Pro-Cyclicality Of Small And Medium Enterprise (Sme) Loans According To Financing Type Based On Purpose: Evidence From Korean Banks - Ji , Yong Seo (Asian Academy of Management (AAM), 2016)
An empirical analysis is conducted on the pro-cyclicality of SME loans based on purpose, which has not been examined in previous research. In this study, the purpose of SME loans is divided into four types: total SME loans, long-term loans for investment in equipment, long-term loans for R&D investment, and short-term loans for working capital. The aim of the study is to determine whether pro-cyclicality exists in the four types of loans. In particular, it is expected that because of the high-risk weight considered in estimating credit risk, the number of long-term loans may have decreased in the economic distress experienced since 2006, when the Basel II accord came into eﬀect. At that time, most banks adopted the advanced internal rating approach to calculate borrowers' credit risks. This study is based on the assumption that the risk weight of long-term loans is diﬀerent from that of short-term loans. The GMM model is adopted to test the pro-cyclicality of long-term and short-term loans. The test results showed signifcant pro-cyclicality in long-term loans for investment in equipment and R&D. Second, there was no pro-cyclicality in short-term loans for purchasing raw materials. Third, the fnancial characteristics aﬀecting the lending behaviour of banks were indicators of proftability and fnancial soundness of credit. Based on the results, eﬀective policies are recommended, such as credit enhancement through credit guarantees, in order to alleviate the eﬀects of pro-cyclicality on long-term loans